Legends of earth, air, fire, and water - Hadley, Eric; Hadley, Tessa; Waldman, Bryna (Cambridge Cambridge University Press, 1985)
A collection of myths and legends from different parts of the world about the four basic elements without which life would not be possible.
Keywords: Mythology -- Juvenile literature; Folklore; Mythology